Corner-based estimation of tire forces and vehicle velocities robust to road conditions - Hashemi, Ehsan; Pirani, Mohammad; Khajepour, Amir; Kasaiezadeh Mahabadi, Seyed Alireza; Chen, Shih-Ken; Litkouhi, Baktiar (Elsevier, 2017)
Recent developments in vehicle stability control and active safety systems have led to an interest in reliable vehicle state estimation on various road conditions. This paper presents a novel method for tire force and velocity estimation at each corner to monitor tire capacities individually. This is entailed for more demanding advanced vehicle stability systems and especially in full autonomous driving in harsh maneuvers. By integrating the lumped LuGre tire model and the vehicle kinematics, it is shown that the proposed corner-based estimator does not require knowledge of the road friction and is robust to model uncertainties. The stability of the time-varying longitudinal and lateral velocity estimators is explored. The proposed method is experimentally validated in several maneuvers on different road surface frictions. The experimental results confirm the accuracy and robustness of the state estimators.
The final publication is available at Elsevier via https://doi.org/10.1016/j.conengprac.2017.01.009 © 2017. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: Vehicle state estimation; Velocity estimation; Tire force estimation; Robust observer design